Optimalisasi Penggunaan TV Interaktif Teknologi di SMAS IT Hasanka Palangka Raya - Pramudya, Ikhwannur Faizin; Ilmiani, Aulia Mustika; Amal, Ichlasul (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This activity was carried out by MBKM students at SMAS IT Hasanka Palangka Raya with the main goal of supporting the implementation of technology-based learning through the optimization of interactive TV use in classrooms. The program originated from the school’s need to provide modern, engaging, and efficient learning experiences while maintaining Islamic values and discipline without allowing the use of personal gadgets in class. The research method employed was Participatory Action Research (PAR), adopting a collaborative, participatory, and reflective approach among MBKM students, teachers, and students through cycles of reflection, action, and evaluation. Data were collected through participatory observation, reflective interviews, and documentation of learning activities. The results show that the use of interactive TVs had a positive impact on the effectiveness of learning and encouraged innovation in teaching practices. MBKM students played an active role in assisting the implementation of educational technology while helping teachers and students adapt to digital media. This activity demonstrates that collaboration between universities and schools can strengthen the digital transformation of education. The recommendation from this activity emphasizes the need for ongoing teacher training and the continuation of MBKM programs to further support innovation in technology-based learning.